Pemberdayaan Masyarakat Peduli Lingkungan Melalui Teknologi Pengolahan Minyak Jelantah Menjadi Lilin Wangi - Maulidah, Rifaatul; Sulistyaningsih, Dwi; Sujarwanto, Eko; Sumantri, Agus (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2024)
The Pawindan Village Community, Ciamis District, has become aware of the importance of preserving the environment. It can be seen from the programs initiated by the Kampung Keluarga Berencana Magot and the Usaha Peningkatan Pendapatan Keluarga Sejahtera Flamboyan, such as the "Save the Environment" program, which implements the mission "Halaman Dirumat jeung Pipir Diurus." Unfortunately, information on technology for processing waste into valuable goods has not yet arrived, especially regarding techniques for processing waste cooking oil. Therefore, introducing this technology is essential to convey through Community Service activities. This activity aims to apply Appropriate Technology to process waste cooking oil into scented candles, which are economically valuable goods. This activity is a solution chosen by the team and partners to provide additional knowledge and skills in utilizing waste materials into valuable products. The method used in training activities is a lecture method, question and answer discussion, followed by a demonstration and practice of processing waste cooking oil into scented candles. The activity results show the Pawindan Village Community's new knowledge about processing waste cooking oil into scented candles. Data was also obtained on participants' responses before and after participating in the activity, which showed that there was positive interest from the community in using this technology. In the future, this program is expected to help the community, especially in Pawindan Village, Ciamis District, to continue to preserve the environment and acquire new skills